Accurate thermomechanical analysis of sandwich beams with nonhomogeneous core by quadrature element method. (October 2022) - Deng, Jian; Zhou, Guangming; Wang, Xinwei
Abstract: Although theoretical analysis of sandwich beam and panel with homogeneous face sheets and functionally graded (FG) core is available, however, accurate modeling and predicting the through-thickness distribution of the shear stress (strain) is still a challenging task. In this paper, an accurate thermomechanical bending analysis of sandwich beams is presented. Elasticity theory is directly employed for the entire sandwich panel to capture the through-thickness distribution of the shear stress (strain) accurately. Explicit formulation of quadrature element method (QEM) with an arbitrary number of nodes and nodes of any type is developed to ease the programming and convergence study. The influence of power-law index, porosity and temperature changes on the deflection, through-thickness distributions of stresses and shear strain is studied. The results may be useful for developing new panel theories and numerical methods. Highlights: A novel modeling strategy for thermomechanical analysis of FGP sandwich beam is presented. Explicit quadrature element formulation with any number and type of node is given. All stress components can be accurately obtained via the constitutive equation. Effect of power-law index, porosity and temperature changes on bending behavior is studied.